2010
DOI: 10.1590/s0100-40422010000400026
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of Salacia elliptica (Celastraceae)

Abstract: Recebido em 6/8/09; aceito em 2/12/09; publicado na web em 25/3/10The chemical investigation of Salacia elliptica allowed to the isolation of 20 constituents: two polyols, one xanthone, a mixture of long chain hydrocarbons, one carboxylic acid, one polymer, two steroidal compounds, one aromatic ester and eleven pentacyclic triterpenes. These triterpenes include 3β-stearyloxy-oleanane, 3β-stearyloxy-ursane, one seco-friedelane, and eight compounds of the friedelane serie. The chemical structure and the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
11
0
3
Order By: Relevance
“…This fact could be related to the higher liposolubility of this pentacyclic triterpene, leading to a higher ability of crossing the host cell membrane. The trypanocidal activity of triterpenes has previously been investigated (Abe et al 2002;Duarte et al 2002;Rosas et al 2007), and structure activity relationship studies revealed that the presence of the carboxyl group at C-17 is required for activity against T. cruzi (Cunha et al 2006;Leite et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…This fact could be related to the higher liposolubility of this pentacyclic triterpene, leading to a higher ability of crossing the host cell membrane. The trypanocidal activity of triterpenes has previously been investigated (Abe et al 2002;Duarte et al 2002;Rosas et al 2007), and structure activity relationship studies revealed that the presence of the carboxyl group at C-17 is required for activity against T. cruzi (Cunha et al 2006;Leite et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The spectral data of all these compounds ( Figure 1) were in agreement with the previously published data, thereby allowing for identification of 16β-hydroxylupane-1,20(29)-dien-3-one (1) (Wei et al 2008), (3β)-3-hydroxyolean-12-en-28-oic acid (2) (Xiao-Qiang et al 2008;Geraldo et al 2008), 3β-hydroxy-olean-5,12-dien-28-oic acid (3) (Choudhary et al 2007;Zhang et al 1993), daucosterol (4) (Duarte et al 2010;Sultana et al 2010;Bayoumi et al 2010), 3-O-β-d-glucopyranosyl-stigmasta-5,11(12)-diene (5) and chlorogenic acid (6) (Kusaura et al 2010 3 OD, showed characteristic signals of two methyl groups at 1.15 ppm (3H, t, J = 7.0 Hz) and 2.57 ppm (3H, br s). Two methoxy groups were observed at 3.21 ppm (6H, br s) and one at 3.70 ppm (3H, br s).…”
Section: Discussionmentioning
confidence: 99%
“…In Amazon, there are several plant species bearing medicinal properties (OSAKADA, 2009), including the species belonging to the Celastraceae family, composed by 98 genera and roughly 1264 species (FONSECA ET AL., 2007;LORENZI & MATOS, 2008;OLIVEIRA et al, 2012), distributed all over the world, particularly in the tropical and subtropical regions, including the north of Africa, South America and Asia (SPIVEY et al, 2002;DUARTE et al, 2010;HURTADO, 2013;MOHAMED & PERWEZ, 2014).…”
Section: Introductionmentioning
confidence: 99%